Metal-based nanomedicines for cancer theranostics - Hai-Jia Yu; Jian-Hua Liu; Wei Liu; Rui Niu; Bin Zhang; Yuan Xiong; Yang Liu; Ying-Hui Wang; Hong-Jie Zhang (Military Medical Research)
Abstract The heterogeneity and invasiveness of cancer cells pose serious challenges in cancer diagnosis and treatment. Advancements and innovations in metal-based nanomedicines provide novel avenues for addressing these challenges. Metal-based nanomedicines possess unique physicochemical properties that enable their interaction with living organisms, thereby inducing complex biological responses. These nanomaterials have been extensively used to enhance the contrast and sensitivity of cancer imaging and to amplify the distinction between cancerous and healthy tissues. Moreover, these nanomaterials can effectively combat a wide spectrum of cancers through various methods, including drug delivery, radiotherapy, photothermal therapy (PTT), photodynamic therapy (PDT), sonodynamic therapy (SDT), biocatalytic therapy, ion interference therapy (IIT), and immunotherapy. Currently, there is still a need for a comprehensive summary on the metal-based nanomaterials for cancer diagnosis and treatment. Herein, we present a systematic and complete overview of action mechanisms and the applications of metal-based nanomaterials in cancer theranostics. A summary of common strategies for synthesizing and modifying metal-based nanomedicines is presented, and their biosafety is analyzed. Then, the latest developments in their applications for cancer imaging and anticancer treatment are provided. Finally, the key technical challenges and reasonable perspectives of metal-based nanomedicines for cancer theranostics in clinical applications are discussed.